1982
DOI: 10.1017/cbo9780511600586
|View full text |Cite
|
Sign up to set email alerts
|

The Core Model

Abstract: The core model, K, is a generalization of Gödel's constructible universe of set theory; K is used to produce 'fine structural' results of a less restrictive kind. This book aims to introduce the core model to those with a basic knowledge of axiomatic set theory. The covering lemma for K is the main technical result but other applications are also considered. The author gives a full exposition of general fine structure and of iterated ultrapowers and concludes the work with a short section on the difficulties e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Since a measurable cardinal is Keisler we may assume that there is no inner model with a measurable cardinal. We shall show that κ is Keisler in the Dodd-Jensen core model K (see [1]). Using our assumption ¬L It can be shown that every Keisler cardinal is inaccessible.…”
Section: Proof (2)mentioning
confidence: 86%
“…Since a measurable cardinal is Keisler we may assume that there is no inner model with a measurable cardinal. We shall show that κ is Keisler in the Dodd-Jensen core model K (see [1]). Using our assumption ¬L It can be shown that every Keisler cardinal is inaccessible.…”
Section: Proof (2)mentioning
confidence: 86%
“…Then D is a good set of indiscernibles of order type c for K λ , ∈ F . We now appeal to the Jensen Indiscernibles Lemma (see [2], 16.10), and use the uncountable cofinality of c, to claim that there is E ⊇ D with E ∈ K and elements of E good indiscernibles for the same structure. But this entails E being a homogeneous set for the function F .…”
Section: Theorem 26mentioning
confidence: 99%
“…j(a) = a for a < k, j(k) > k and M is closed under sequences of its elements of length < /(k). 1. The forcing notion.…”
mentioning
confidence: 99%